Evaluation of degradability of Moringa, Pineapple waste and Plantain herbs by in situ and in vitro gas production technique (Bangladesh Journal of Animal Science, 2023)
Nutritional evaluation of feed ingredients is important for potential use in feed rations. It is very important to determine not only the nutrient content and quality of feeds but also their digestibility prior to adding in the ration. This study was undertaken to assess the potential nutritive value of selected shade-dried herbs of moringa, pineapple waste, and plantain through in situ degradation and in vitro gas production techniques. The study compared 4 treatments, namely moringa (MH), pineapple waste (PwH), plantain (PH) herbs, and a combination of three of them with a ratio of 1:1:1 (MxH). The rumen dry matter (DM) and crude protein (CP) degradability kinetics were analyzed by using the nylon bags (in situ) procedure and the organic matter digestibility and fermentation characteristics were analyzed by in vitro gas production technique. The results of the in situ study revealed that the ruminal dry matter disappearance differed significantly (P